Who’s Afraid of Literature? Rhetorical Routines in Literary Research Articles - Balocco, Anna Elizabeth (The ESPecialist, 2012)
This article is broadly concerned with disciplinary variation in written academic discourse. It takes as its object of study the genre specialized academic article in the area of literary research in English, an area which has been relatively neglected in current linguistic research. Aspects of rhetorical routines in literary research articles are dealt with, on the basis of an investigation of a corpus of 20 published articles, in genre-analytic terms. The research findings allow us to make the following claims. There seems to be less epistemic accounting in literary research than in other disciplinary areas, which might be accounted for in terms of its characteristics as a “rural” domain (Becher, 1989). This lends support to a previous claim by McDonald (1994), based on analyses of a small corpus of 4 articles in one sub-field of literary research. Where there is epistemically-focused work, however, the moves proposed by Swales (1990) in his CARS model proved to be effective analytical categories to account for rhetorical routines in literary research.